The Influence of BMI and Self-Efficacy Levels on the Accuracy in Self-Reported Physical Activity Recall - Graves, Brooke (East Carolina University, 2011)
The purpose of this study was to compare self-reported and objectively measured physical activity levels among college students with different body mass index (BMI) classifications (normal weight and overweight/obese), in order to determine if BMI influences physical activity recall accuracy. A secondary purpose was to examine the accuracy in physical activity recall by physical activity self-efficacy. On day one, 52 college students completed the Marlow Crowne Social Desirability Questionnaire, a moderate physical activity self-efficacy questionnaire, a vigorous physical activity self-efficacy questionnaire, and received an ActiGraph GT1M accelerometer to wear for 7 consecutive days. After wearing the accelerometer, participants completed self-report physical activity measures including the Behavior Risk Factor Surveillance Survey (BRFSS) and the International Physical Activity Questionnaire (IPAQ). They also completed a self-efficacy towards physical activity recall questionnaire. No significant difference was found between the average minutes per day spent in moderate and vigorous physical activity by normal and overweight/obese groups for the BRFSS, IPAQ and ActiGraph GT1M. Also, recall accuracy was similar between the normal weight and overweight/obese participants on the BRFSS and IPAQ questionnaires. No significant relationship was found between moderate physical activity self-efficacy and recall accuracy on either the IPAQ or BRFSS. However, vigorous physical activity self-efficacy was positively related to recall accuracy on both the IPAQ and BRFSS. These results suggest that BMI does not affect either the amount of physical activity completed or recall accuracy in college students. In contrast, vigorous physical activity self-efficacy influences recall accuracy of vigorous physical activity.
Keywords: Kinesiology; College students; Obesity; Physical activity; Recall accuracy; Self-perception; Exercise--Psychological aspects; Self-evaluation; Self-efficacy; Body image; Body mass index